2017
DOI: 10.1038/ncomms15598
|View full text |Cite
|
Sign up to set email alerts
|

A reaction mode of carbene-catalysed aryl aldehyde activation and induced phenol OH functionalization

Abstract: The research in the field of asymmetric carbene organic catalysis has primarily focused on the activation of carbon atoms in non-aromatic scaffolds. Here we report a reaction mode of carbene catalysis that allows for aromatic aldehyde activation and remote oxygen atom functionalization. The addition of a carbene catalyst to the aldehyde moiety of 2-hydroxyl aryl aldehyde eventually enables dearomatization and remote OH activation. The catalytic process generates a type of carbene-derived intermediate with an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 53 publications
0
42
0
Order By: Relevance
“…[11b] Following these studies,s everal approaches to extend this reactivity to carbocyclic aromatic systems have emerged. [13] These contributions have expanded the scope of carbene catalysis,w hile simultaneously presenting opportunities to develop new and complementary methods employing NHC-bound o-QDMlike nucleophiles.H erein, we report ad ecarboxylative transformation proceeding via an NHC-bound aza-o-QM intermediate to access enantioenriched dihydrobenzoxazin-4-ones (Scheme 1c). There have been significantly fewer developments employing oquinone methides (o-QMs) or aza-o-quinone methides (azao-QMs) as nucleophiles in NHC catalysis.Anotable recent advance by Chi employed salicylaldehydes in the presence of stoichiometric oxidant and base to generate an NHC-bound o-QM, which participated in an annulation with trifluoromethyl ketone electrophiles (Scheme 1b).…”
mentioning
confidence: 99%
“…[11b] Following these studies,s everal approaches to extend this reactivity to carbocyclic aromatic systems have emerged. [13] These contributions have expanded the scope of carbene catalysis,w hile simultaneously presenting opportunities to develop new and complementary methods employing NHC-bound o-QDMlike nucleophiles.H erein, we report ad ecarboxylative transformation proceeding via an NHC-bound aza-o-QM intermediate to access enantioenriched dihydrobenzoxazin-4-ones (Scheme 1c). There have been significantly fewer developments employing oquinone methides (o-QMs) or aza-o-quinone methides (azao-QMs) as nucleophiles in NHC catalysis.Anotable recent advance by Chi employed salicylaldehydes in the presence of stoichiometric oxidant and base to generate an NHC-bound o-QM, which participated in an annulation with trifluoromethyl ketone electrophiles (Scheme 1b).…”
mentioning
confidence: 99%
“…Lewis acids have been shown to be promising co‐catalysts that can enhance stereoselective control in multiple NHC‐catalytic reactions . We therefore examined Lewis acids as co‐catalysts (entries 5–7) and found that the addition of urea molecule G could succefully enhance the reaction er from 86:14 (entry 4) to 90:10 (entry 7). Organic or inorganic bases with strong basicities resulted in a decomposition of the N , O ‐acetal products (entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…The carbon atoms were activated as either nucleophilic or electrophilic reactive centers. In 2017, Chi and co‐workers found that through the addition of a carbene to the aldehyde moiety of a 2‐hydroxyl benzaldehyde under oxidative conditions, the phenol oxygen atom could be activated for enantioselective reactions . This activation converted the acylazolium to an ortho ‐quinone methide ( o ‐QM) intermediate with the oxygen as the reactive center (Scheme b, left).…”
Section: Introductionmentioning
confidence: 99%
“…When the reaction of 1 a and 2 a was performed in the absence of NHC pre‐catalyst 4 , the desired product 3 a was not formed indicating the role of NHC in this [6+2] annulation (Scheme , eq 6). Moreover, the acetal 10 a (likely formed by the N−H addition of 1 a to 2 a followed by intramolecular cyclization) was not observed under these conditions showing that the direct N−H addition of initially formed acylazolium and cyclization in a [3+2] pathway is not operating in this case . In addition, when the reaction was performed using N ‐Boc protected aldehyde 11 a , the product 3 a was not formed signifying the role of N−H moiety in forming the NHC‐bound cross‐conjugated aza‐trienolates (eq 7).…”
Section: Methodsmentioning
confidence: 99%